Penerapan Terapi Bermain Puzzle dalam Menurunkan Ansietas Akibat Hospitalisasi Anak Prasekolah dengan Dengue Hemorrhagic Fever - Maria Indrawati; Ketut Suryani; Veroneka Yosefpa Windahandayani (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2026)
Hospitalization is a condition that requires a child to be admitted to the hospital. This situation causes children to experience anxiety, restlessness, and fear. One of the nursing interventions to reduce anxiety due to hospitalization is play therapy. A form of play therapy appropriate for preschool children is puzzle play therapy. Puzzle play therapy is an activity in which children arrange pieces of pictures or specific shapes to form a complete image. This therapy encourages children to develop patience, stimulates concentration, and provides feelings of comfort and enjoyment, thereby reducing anxiety. The method used in preparing this Final Nursing Scientific Paper was a descriptive case study with the implementation of puzzle play therapy. The respondents consisted of three children experiencing anxiety due to hospitalization. Puzzle play materials and the Facial Image Scale (FIS) were used as measurement tools. The intervention was conducted over three consecutive days, with a duration of 15 minutes per session. The results showed a decrease in anxiety levels after puzzle play therapy: respondent 1 decreased from anxiety scale 5 to scale 1, respondent 2 from scale 4 to scale 1, and respondent 3 from scale 5 to scale 1. It can be concluded that puzzle play therapy is effective in reducing anxiety due to hospitalization in preschool children with dengue hemorrhagic fever. The implementation of puzzle play therapy is expected to become a routine nursing intervention to reduce hospitalization-related anxiety in preschool children with dengue hemorrhagic fever.